background image

18.3. COMPLETE STAROIDS AND MULTIFUNCOIDS

286

1

.

F ∈

P

.

2

.

F

is a complete free star on

P

.

3

.

?

F

is a complete free star on

F

.

Theorem

1476

.

Let

Z

be a boolean lattice. For any set

S

P

P

there exists

a principal filter

A

such that

A

=

S

iff

S

is a complete free star (on

P

).

Proof.

. From the previous theorem.

.

P

/

S

and

F

T

S

T

S

6

=

∅ ⇔ ∃

X

T

:

X

S

. Take

A

=

n

X

X

P

\

S

o

.

We will prove that

A

is a principal filter. That

A

is a filter follows from

properties of free stars. It remains to show that

A

is a principal filter. It

follows from the following equivalence:

P

l

A ∈ A ⇔

P

G

h¬i

A ∈ A ⇔

P

G

h¬i

A

/

S

¬∃

X

∈ h¬i

A

:

X

S

⇔ ∀

X

∈ h¬i

A

:

X /

S

⇔ ∀

X

∈ A

:

X

∈ A ⇔

1

.

Proposition

1477

.

1

. If

S

is a free star on

A

then

S

is a free star on

Z

, provided that

Z

is a

join-semilattice and the filtrator (

A

;

Z

) is down-aligned and with finitely

join-closed core.

2

. If

S

is a free star on

P

then

S

is a free star on

F

, provided that

Z

is a

boolean lattice.

Proof.

1

.

X

t

Z

Y

S

X

t

Z

Y

S

X

t

A

Y

S

X

S

Y

S

X

S

Y

S

for every

X, Y

Z

; 0

/

S

is obvious.

2

There exists a filter

F

such that

S

=

F

. For every filters

X

,

Y ∈

F

X t

A

Y ∈

S

up(

X t

A

Y

)

S

⇔ ∀

K

up(

X t

F

Y

) :

K

F ⇔

K

up(

X t

F

Y

) :

K

6 F ⇔ X t

F

Y 6 F ⇔ X t

F

Y ∈

?

F ⇔ X ∈

?

F ∨ Y ∈

?

F ⇔

X 6 F ∨ Y 6 F ⇔ ∀

X

up

X

:

X

6 F ∨ ∀

Y

up

Y

:

Y

6 F ⇔

X

up

X

:

X

F ∨ ∀

Y

up

Y

:

Y

F ⇔

up

X ⊆

S

up

Y ⊆

S

⇔ X ∈

S

∨ Y ∈

S

;

⊥ ∈

S

up

⊥ ⊆

S

⇔ ⊥ ∈

S

what is false.

Corollary

1478

.

If

S

is a free star on

F

then

S

is a free star on

P

, provided

that

Z

is a join-semilattice.

Proposition

1479

.

1

. If

S

is a complete free star on

A

then

S

is a complete free star on

Z

, provided that

Z

is a complete lattice and the filtrator (

A

;

Z

) is down-

aligned and with join-closed core.

2

. If

S

is a complete free star on

P

then

S

is a complete free star on

F

,

provided that

Z

is a boolean lattice.

Proof.

1

.

F

Z

T

S

F

Z

T

S

F

A

T

S

T

S

6

=

∅ ⇔

T

S

6

=

for

every

T

P

Z

;

/

S

is obvious.